Aspergillus Mycotoxins: The Major Food Contaminants - Mengyao Xue; Zheng Qu; Antonio Moretti; Antonio F. Logrieco; Haiyan Chu; Qi Zhang; Changpo Sun; Xianfeng Ren; Li Cui; Qinglin Chen; Yi An; Chengjun Li; et al. (Advanced Science)
Abstract Mycotoxins, a category of fungal secondary metabolites, frequently contaminate food products and pose a severe threat to human health. Aspergillus, a genus of fungi, is capable of producing mycotoxins, with aflatoxins (AFs) and ochratoxins being its principal types. Aspergillus mycotoxins can contaminate a wide range of crops and their derivatives, such as maize, wheat, rice, minor cereals, and peanuts, thereby threatening food and feed safety. In the paper, the related biosynthesis genes and multifaceted biosynthesis pathways of these mycotoxins are first discussed in detail, and elucidated several global regulators, including growth conditions, oxidative stress, and cell signal. Furthermore, how global shifts in temperature and water availability, driven by climate change (including rising temperatures, increased heavy rainfall frequency, prolonged droughts, and elevated carbon dioxide levels), are key determinants of Aspergillus proliferation and mycotoxin production are explored. Finally, to safeguard animal and human health from the detrimental impacts of Aspergillus mycotoxins, the effective and convenient analytical techniques and management strategies for the detection and prevention of contamination are analyzed. Overall, this review provides effective detection techniques and promising solutions to the global contamination of food with Aspergillus mycotoxins, which is of great significance to ensuring food security and protecting people's lives and health.